Del gobierno reactivo al gobierno proactivo: Alcances, limitaciones y resguardos - Oszlak, Oscar (Revista del CLAD Reforma y Democracia, 2025)
The digitalization of public administration has been developing at an increasingly accelerated pace. In particular, it is noteworthy the impact produced by the combination of interoperability between systems and databases with generative artificial intelligence, which among other things, allow governments to deliver increasingly personalized services to citizens, so that public management is gradually moving from a long stage in which it satisfied the needs and demands of citizens reactively, to one in which technology allows anticipating the demand of users proactively. This paper analyzes the scope of this technological transition in public management, the restrictions of its possible adoption in technologically lagging countries, and the safeguards that should be considered from the point of view of cybersecurity, privacy of individual data, and possible risks to democratic life.